Preparation method of graded lithium-iron position co-doped high-compaction lithium iron phosphate
Through the co-doping method of graded lithium iron, iron phosphate and iron phosphate of ammonium method are mixed with iron phosphate and lithium and iron dopants are added, which achieves the coordinated improvement of high-pressure lithium iron phosphate, and solves the problems of complex production processes and harsh conditions in the existing technology, which is suitable for mass production.
Patent Information
- Application Number
- CN202510087074.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The existing preparation methods for high-pressure lithium iron phosphate have complex production processes and harsh production conditions, making it difficult to achieve mass production.
The method of graded lithium iron-position co-doping is used to mix the ammonium iron phosphate and sodium iron phosphate, and the wet slurry is graded, and lithium-position dopant and iron-position dopant are added to prepare high-pressure lithium iron phosphate by one sintering.
The compaction density and specific capacity of lithium iron phosphate positive electrode material are achieved, the high-rate electrical performance is improved, the production cost is reduced, and the process is simplified, which is suitable for mass production.
Smart Images

Figure CN119873780A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a method for preparing graded lithium-iron co-doped high-density lithium iron phosphate. Background Art
[0002] With the rapid development of the power battery and electrochemical energy storage market, the market demand for high-safety, long-life, and long-cycle lithium-ion batteries is becoming increasingly strong. Among them, lithium iron phosphate cathode materials have become the lithium battery cathode materials with the highest market share due to their advantages such as high safety, high capacity, long cycle and low cost. However, the energy density of lithium iron phosphate cathode materials is lower than that of ternary cathode materials, which restricts their application in high-end power batteries.
[0003] The existing technology usually uses the method of increasing compaction density and specific capacity to improve the energy density of lithium iron phosphate. Particle grading can effectively increase the compaction density of lithium iron phosphate. Chinese patent CN118419889A discloses a high-density graded lithium iron phosphate and its preparation method and application. First, doped iron phosphate with different iron-phosphorus ratios is selected, mixed and divided into two parts, lithium source, carbon source, conductive agent, dispersant and solvent are added to each part respectively, and stirred to obtain precursor slurry A and precursor slurry B; then the precursor slurry A is ground to D50 of 0.15-0.20μm, and the precursor slurry B is ground to D50 of 0.25-0.40μm; the ground precursor slurry A and precursor slurry B are mixed and spray dried and air flow crushed in turn to obtain a lithium iron phosphate precursor; finally, the lithium iron phosphate precursor is sintered to obtain a high-density graded lithium iron phosphate. This patent uses a slurry grading method to achieve a synergistic improvement in the compaction density and specific capacity of lithium iron phosphate. However, due to the use of a secondary sintering process, the production process is complicated and the production cost is high.
[0004] Chinese patent CN111392705A discloses a method for preparing high-density lithium iron phosphate, firstly, iron phosphate with an iron-phosphorus ratio of 0.98-0.985 and an iron-phosphorus ratio of 0.965-0.97 is mixed with a lithium source and a carbon source and ground in water to form a mixed slurry, and then the mixed slurry is spray-dried, sintered, and airflow-pulverized in sequence to obtain lithium iron phosphate. This patent adopts a one-time sintering process, which simplifies the production process and reduces the production cost, but the high-rate electrical properties and compacted density of lithium iron phosphate are greatly affected by the mass ratio of large and small particles, and the mass ratio of large and small particles needs to be strictly controlled. The production conditions are relatively harsh and it is difficult to achieve mass production. Summary of the invention
[0005] In view of the technical problems that the existing preparation methods of high-compacted lithium iron phosphate have complex production procedures and harsh production conditions, making it difficult to achieve mass production, the present invention provides a preparation method of graded lithium-iron co-doped high-compacted lithium iron phosphate, which achieves a synergistic improvement in the compaction density and specific capacity of the lithium iron phosphate positive electrode material by mixing two parts of iron phosphate with different iron-phosphorus ratios and performing wet slurry grading; lithium dopants and iron dopants are added in the process of preparing the mixed slurry, thereby improving the high-rate performance of the lithium iron phosphate positive electrode material.
[0006] The technical solution of the present invention is as follows: A method for preparing graded lithium-iron co-doped high-density lithium iron phosphate comprises the following steps: Step 1: After mixing ammonium ferric phosphate and sodium ferric phosphate, a mixed ferric phosphate is obtained, and the mixed ferric phosphate is mixed with a lithium source, a carbon source, a dispersant, a metal dopant and a solvent to obtain a mixed slurry, wherein the iron-phosphorus ratio of the ammonium ferric phosphate is 0.97-0.98, the iron-phosphorus ratio of the sodium ferric phosphate is 0.96-0.965, and the metal dopant includes an iron-site dopant and a lithium-site dopant; Step 2: The mixed slurry is divided into slurry 1 and slurry 2, and the slurry 1 and slurry 2 are ground respectively, the grinding particle size D50 of slurry 1 is 0.2-0.3 μm, and the grinding particle size D50 of slurry 2 is 0.6-1.1 μm; Step 3: Evenly mix the ground slurry 1 and the ground slurry 2, and then spray dry, sinter and jet mill in sequence to obtain graded lithium-iron co-doped high-density lithium iron phosphate.
[0007] Furthermore, in step one, the lithium source is any one of lithium carbonate, lithium hydroxide and lithium dihydrogen phosphate; the carbon source is any one or more of glucose, sucrose, PVDF, and graphene; the dispersant is any one of PEG2000, PEG6000, and PVA2000; the iron-site dopant is any one of titanium dioxide, ammonium metavanadate, magnesium acetate, aluminum oxide, and niobium oxide; the lithium-site dopant is any one of sodium carbonate, potassium carbonate, sodium hydroxide, and potassium hydroxide; and the solvent is pure water or ethanol.
[0008] Furthermore, in step one, the molar ratio of the mixed iron phosphate, lithium source and metal dopant is iron element: phosphorus element: lithium element: metal element in the metal dopant = 0.95-1: 1-1.1: 1-1.1: 0.005-0.05, and the mass ratio of the mixed iron phosphate, carbon source and dispersant is mixed iron phosphate: carbon source: dispersant = 1: 0.01-0.1: 0.01-0.1; the solid content of the mixed slurry is 38%-45%.
[0009] Furthermore, in step 1, the mass ratio of ammonium ferric phosphate to sodium ferric phosphate is 1:1.
[0010] Furthermore, in step 2, the mass ratio of slurry 1 to slurry 2 is 1-3:1.
[0011] Furthermore, in step 2, a sand mill is used for grinding, the rotation speed of the sand mill is 2400-2600 r / min, preferably 2500 r / min, and the grinding temperature is lower than 40°C.
[0012] Furthermore, in step three, the ground slurry one and the ground slurry two are evenly mixed by stirring; the inlet air temperature of the spray drying is 200-240°C, the outlet air temperature of the spray drying is 75-110°C, and the water content of the material obtained by spray drying is less than 3wt%.
[0013] Furthermore, in step three, sintering is carried out under the protection of nitrogen or argon, the sintering heating rate is 2-5°C / min, the sintering temperature is 700-820°C, and the sintering time is 6-10h.
[0014] Furthermore, in step three, the particle size D50 of the high-density lithium iron phosphate is 0.8-1.4 μm.
[0015] Furthermore, the solid content of the slurry obtained after mixing in step three is 35%-45%.
[0016] The beneficial effects of the present invention are: The invention provides a method for preparing a graded lithium-iron co-doped high-density lithium iron phosphate, wherein ammonium-based iron phosphate with a high iron-phosphorus ratio and sodium-based iron phosphate with a low iron-phosphorus ratio are mixed to prepare a mixed slurry. Since the iron phosphate prepared by the ammonium process has good electrochemical performance and the iron phosphate prepared by the sodium process has a high compaction density, the ammonium-based iron phosphate with a high iron-phosphorus ratio and the sodium-based iron phosphate with a low iron-phosphorus ratio are mixed to achieve not only the gradation between the primary particles of the iron phosphate, but also the synergistic improvement of the electrochemical performance and compaction density of the lithium iron phosphate positive electrode material; an iron-based dopant and a lithium-based dopant are added to the mixed slurry, and different types of doping ions are doped at different sites of the lithium iron phosphate crystal structure, and the lithium / iron-based co-doping is used to give full play to the synergistic effect, thereby broadening the Li + The one-dimensional diffusion channel of Li + It has a faster deintercalation rate, and enhances electronic conductivity by reducing the band gap and generating a mixed valence state, which is beneficial to the transition of electrons between iron and doped ions, thereby improving the electrochemical performance of the iron-doped positive electrode, especially improving the electrochemical performance of the lithium iron phosphate positive electrode material under high current density. The present invention can prepare a lithium iron phosphate positive electrode material with a high compaction density and a high specific capacity by sintering in only one step, which significantly reduces the production cost. At the same time, the present invention can achieve mass production based on the existing lithium iron phosphate production line, without increasing the investment in additional equipment, and can quickly realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 1.
[0019] Figure 2 This is the first charge and discharge curve of the lithium iron phosphate positive electrode material prepared in Example 1 at 0.1C. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0021] Example 1 A method for preparing graded lithium-iron co-doped high-density lithium iron phosphate comprises the following steps: Step 1: After mixing ammonium ferric phosphate and sodium ferric phosphate in a mass ratio of 1:1, a mixed ferric phosphate is obtained. 1000g of mixed ferric phosphate, 253.6g of lithium carbonate, 50g of sucrose, 80g of PEG6000, 6.45g of titanium dioxide and 2.03g of sodium carbonate are added to 2L of pure water, and then 4.5g of 85% phosphoric acid is added to the mixed solution as a sintering aid, and mechanically stirred for 30 minutes to mix evenly to obtain a mixed slurry. Among them, the iron-phosphorus ratio of sodium ferric phosphate is 0.962, and the iron-phosphorus ratio of ammonium ferric phosphate is 0.973.
[0022] Step 2: The mixed slurry is divided into slurry 1 and slurry 2 at a mass ratio of 7:3, and slurry 1 and slurry 2 are respectively ball-milled using a sand mill, slurry 1 is ball-milled to a D50 of 0.25 μm, and slurry 2 is ball-milled to a D50 of 0.86 μm. The speed of the sand mill is 2500 r / min, and during the ball milling process, the temperature of the slurry is controlled to be below 40°C.
[0023] Step 3: Mix the ground slurry 1 and the ground slurry 2 evenly by stirring, and then spray dry to obtain a spray material. The inlet temperature of the spray drying is 230°C, the outlet temperature of the spray drying is 95°C, and the water content of the spray material is less than 3wt%. The spray material is transferred to a box furnace and kept at 800°C for 9 hours at a heating rate of 3°C / min under a nitrogen atmosphere. The sintered material is crushed by a jet mill, and the particle size D50 of the crushed material is controlled to be 1.2±0.1μm. Finally, after the magnetic screening process, a graded lithium-iron co-doped high-density lithium iron phosphate positive electrode material is obtained.
[0024] Example 2 A method for preparing graded lithium-iron co-doped high-density lithium iron phosphate comprises the following steps: Step 1: After mixing ammonium ferric phosphate and sodium ferric phosphate in a mass ratio of 1:1, a mixed ferric phosphate is obtained. 1000g of mixed ferric phosphate, 253.3g of lithium carbonate, 60g of glucose, 80g of PEG6000, 6.45g of ammonium metavanadate and 2.88g of potassium carbonate are added to 2L of pure water, and then 4.5g of 85% phosphoric acid is added to the mixed solution as a sintering aid, and mechanically stirred for 30 minutes to mix evenly to obtain a mixed slurry. Among them, the iron-phosphorus ratio of sodium ferric phosphate is 0.96, and the iron-phosphorus ratio of ammonium ferric phosphate is 0.98.
[0025] Step 2: The mixed slurry is divided into slurry 1 and slurry 2 at a mass ratio of 6:4, and slurry 1 and slurry 2 are respectively ball-milled using a sand mill, slurry 1 is ball-milled to a D50 of 0.28 μm, and slurry 2 is ball-milled to a D50 of 0.75 μm. The speed of the sand mill is 2500 r / min, and during the ball milling process, the temperature of the slurry is controlled to be below 40°C.
[0026] Step 3: Mix the ground slurry 1 and the ground slurry 2 evenly by stirring, and then spray dry to obtain a spray material. The inlet temperature of the spray drying is 230°C, the outlet temperature of the spray drying is 95°C, and the water content of the spray material is less than 3wt%. The spray material is transferred to a box furnace and kept at 790°C for 9 hours at a heating rate of 3°C / min under a nitrogen atmosphere. The sintered material is crushed by a jet mill, and the particle size D50 of the crushed material is controlled to be 1.2±0.1μm. Finally, after the magnetic screening process, a graded lithium-iron co-doped high-density lithium iron phosphate positive electrode material is obtained.
[0027] Example 3 A method for preparing graded lithium-iron co-doped high-density lithium iron phosphate comprises the following steps: Step 1: After mixing ammonium ferric phosphate and sodium ferric phosphate in a mass ratio of 1:1, a mixed ferric phosphate is obtained. 1000g of mixed ferric phosphate, 253.5g of lithium carbonate, 50g of sucrose, 90g of PEG2000, 6.45g of titanium dioxide and 1.01g of sodium carbonate are added to 2L of pure water, and then 4.5g of 85% phosphoric acid is added to the mixed solution as a sintering aid, and mechanically stirred for 30 minutes to mix evenly to obtain a mixed slurry. Among them, the iron-phosphorus ratio of sodium ferric phosphate is 0.965, and the iron-phosphorus ratio of ammonium ferric phosphate is 0.973.
[0028] Step 2: The mixed slurry is divided into slurry 1 and slurry 2 at a mass ratio of 6:4, and slurry 1 and slurry 2 are respectively ball-milled using a sand mill, slurry 1 is ball-milled to a D50 of 0.28 μm, and slurry 2 is ball-milled to a D50 of 0.65 μm. The speed of the sand mill is 2500 r / min, and during the ball milling process, the temperature of the slurry is controlled to be below 40°C.
[0029] Step 3: Mix the ground slurry 1 and the ground slurry 2 evenly by stirring, and then spray dry to obtain a spray material. The inlet temperature of the spray drying is 230°C, the outlet temperature of the spray drying is 95°C, and the water content of the spray material is less than 3wt%. The spray material is transferred to a box furnace and kept at 795°C for 9 hours at a heating rate of 3°C / min under a nitrogen atmosphere. The sintered material is crushed by a jet mill, and the particle size D50 of the crushed material is controlled to be 1.2±0.1μm. Finally, after the magnetic screening process, a graded lithium-iron co-doped high-density lithium iron phosphate positive electrode material is obtained.
[0030] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is only in step 2: ball milling slurry 1 to a D50 of 0.35 μm, and ball milling slurry 2 to a D50 of 1.5 μm.
[0031] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is only in step 1: using 10.4 g of graphene to replace titanium dioxide and sodium carbonate.
[0032] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the mixed ferric phosphate in step 1 is replaced by ammonium ferric phosphate with an iron-to-phosphorus ratio of 0.97.
[0033] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the mixed ferric phosphate in step 1 is replaced by sodium-process ferric phosphate with an iron-to-phosphorus ratio of 0.965.
[0034] Test Example 1 Compacted Density Test The compaction density test of the lithium iron phosphate positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-4 was performed using a compaction density meter. The test pressure was 3T. The test results are shown in Table 1.
[0035] Test Example 2 Microstructure Test and Electrochemical Performance Test The lithium iron phosphate positive electrode material prepared in Example 1 was tested by scanning electron microscopy. Figure 1 As shown. Figure 1 It can be seen that in the prepared lithium iron phosphate positive electrode material sample, large and small particles are evenly distributed, the particle size distribution is wide, and the particles are spherical; when densely stacked, small particles can be embedded in the gaps between large particles, and the particle size grading between large and small particles can significantly improve the compaction density of the sample in Example 1.
[0036] The lithium iron phosphate positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-4 were respectively subjected to the following operations: dispersed in NMP solution according to the mass ratio of active material: binder PVDF: conductive additive SP = 95:2.5:2.5, mixed evenly and configured into slurry, coated on aluminum foil, vacuum dried, rolled, and cut into pieces to obtain positive electrode sheets. The mass of the active material in the positive electrode sheet is about 12 mg. The negative electrode uses a metal lithium sheet, the diaphragm is a polypropylene porous membrane, and the electrolyte is 1 mol / L LiPF6 / EC+DEC+DMC (wherein the volume ratio EC:DEC:DMC=1:1:1). The charge and discharge specific capacity was tested at a voltage range of 2.0V-3.75V, and the test results are shown in Table 1.
[0037] The first charge and discharge curve of the lithium iron phosphate cathode material prepared in Example 1 at 0.1C is as follows: Figure 2 shown.
[0038] Table 1 Compacted density test and electrochemical performance test results of Examples 1-3 and Comparative Examples 1-4
[0039] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A method for preparing graded lithium-iron co-doped high-density lithium iron phosphate, characterized in that: The steps include: Step 1: After mixing ammonium ferric phosphate and sodium ferric phosphate, a mixed ferric phosphate is obtained, and the mixed ferric phosphate is mixed with a lithium source, a carbon source, a dispersant, a metal dopant and a solvent to obtain a mixed slurry, wherein the iron-phosphorus ratio of the ammonium ferric phosphate is 0.97-0.98, the iron-phosphorus ratio of the sodium ferric phosphate is 0.96-0.965, and the metal dopant includes an iron-site dopant and a lithium-site dopant; Step 2: The mixed slurry is divided into slurry 1 and slurry 2, and the slurry 1 and slurry 2 are ground respectively, the grinding particle size D50 of slurry 1 is 0.2-0.3 μm, and the grinding particle size D50 of slurry 2 is 0.6-1.1 μm; Step 3: Evenly mix the ground slurry 1 and the ground slurry 2, and then spray dry, sinter and jet mill in sequence to obtain graded lithium-iron co-doped high-density lithium iron phosphate.
2. The method for preparing graded lithium-iron co-doped high-density lithium iron phosphate according to claim 1, characterized in that: In step 1, the lithium source is any one of lithium carbonate, lithium hydroxide and lithium dihydrogen phosphate; the carbon source is any one or more of glucose, sucrose, PVDF, and graphene; the dispersant is any one of PEG2000, PEG6000 and PVA2000; the iron-site dopant is any one of titanium dioxide, ammonium metavanadate, magnesium acetate, aluminum oxide and niobium oxide; the lithium-site dopant is any one of sodium carbonate, potassium carbonate, sodium hydroxide and potassium hydroxide; and the solvent is pure water or ethanol.
3. The method for preparing graded lithium-iron co-doped high-density lithium iron phosphate according to claim 1, characterized in that: In step one, the molar ratio of the mixed iron phosphate, lithium source and metal dopant is iron element: phosphorus element: lithium element: metal element in the metal dopant = 0.95-1: 1-1.1: 1-1.1: 0.005-0.05, and the mass ratio of the mixed iron phosphate, carbon source and dispersant is mixed iron phosphate: carbon source: dispersant = 1: 0.01-0.1: 0.01-0.1; the solid content of the mixed slurry is 38%-45%.
4. The method for preparing graded lithium-iron co-doped high-density lithium iron phosphate according to claim 1, characterized in that: In step 1, the mass ratio of ammonium ferric phosphate to sodium ferric phosphate is 1:
1.
5. The method for preparing graded lithium-iron co-doped high-density lithium iron phosphate according to claim 1, characterized in that: In step 2, the mass ratio of slurry 1 to slurry 2 is 1-3:
1.
6. The method for preparing graded lithium-iron co-doped high-density lithium iron phosphate according to claim 1, characterized in that: In step 2, a sand mill is used for grinding, and the grinding temperature is lower than 40°C.
7. The method for preparing graded lithium-iron co-doped high-density lithium iron phosphate according to claim 1, characterized in that: In step three, the ground slurry one and the ground slurry two are mixed evenly by stirring; the inlet air temperature of the spray drying is 200-240°C, the outlet air temperature of the spray drying is 75-110°C, and the water content of the material obtained by spray drying is less than 3wt%.
8. The method for preparing graded lithium-iron co-doped high-density lithium iron phosphate according to claim 1, characterized in that: In step three, sintering is carried out under the protection of nitrogen or argon, the sintering temperature is 700-820° C., and the sintering time is 6-10 hours.
9. The method for preparing graded lithium-iron co-doped high-density lithium iron phosphate according to claim 1, characterized in that: In step 3, the particle size D50 of the high-density lithium iron phosphate is 0.8-1.4 μm.
10. The method for preparing graded lithium-iron co-doped high-density lithium iron phosphate according to claim 1, characterized in that: The solid content of the slurry obtained after mixing in step 3 is 35%-45%.
Citation Information
Patent Citations
Preparation method of high-compaction lithium iron phosphate
CN111392705A
High-compaction graded lithium iron phosphate as well as preparation method and application thereof
CN118419889A
Cited By
Preparation method of multi-stage grading high-compaction lithium iron phosphate
CN120423517A